2016
DOI: 10.1152/ajpregu.00033.2016
|View full text |Cite
|
Sign up to set email alerts
|

The role of the rectum in osmoregulation and the potential effect of renoguanylin on SLC26a6 transport activity in the Gulf toadfish (Opsanus beta)

Abstract: Ruhr IM, Takei Y, Grosell M. The role of the rectum in osmoregulation and the potential effect of renoguanylin on SLC26a6 transport activity in the Gulf toadfish (Opsanus beta). Am J Physiol Regul Integr Comp Physiol 311: R179 -R191, 2016. First published March 30, 2016 doi:10.1152/ajpregu.00033.2016.-Teleosts living in seawater continually absorb water across the intestine to compensate for branchial water loss to the environment. The present study reveals that the Gulf toadfish (Opsanus beta) rectum plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
5
15
0
Order By: Relevance
“…Therefore, understanding the mechanisms of intestinal Zn uptake in fish is of considerable interest from both nutritional and toxicological perspectives. Studies suggested a morpho-functional specialisation of intestinal regions in fish with regard to ion transport (8)(9)(10) , and fish showed anterior-middle regionalisation of ion transport (11) . However, the mechanisms of absorption of mineral elements along the intestinal tract are far less understood (9,12) .…”
mentioning
confidence: 99%
“…Therefore, understanding the mechanisms of intestinal Zn uptake in fish is of considerable interest from both nutritional and toxicological perspectives. Studies suggested a morpho-functional specialisation of intestinal regions in fish with regard to ion transport (8)(9)(10) , and fish showed anterior-middle regionalisation of ion transport (11) . However, the mechanisms of absorption of mineral elements along the intestinal tract are far less understood (9,12) .…”
mentioning
confidence: 99%
“…On the apical membrane of intestinal epithelial cells, Pat-1 may play an important role in HCO 3 - secretion as its stoichiometry is n HCO 3 - /1Cl - as shown in the euryhaline pufferfish, Takifugu obscurus (Kato et al, 2009), although there are conflicting reports on the stoichiometry of Pat-1 in mammals (see Alper and Sharma, 2013). In fact, pat1 is profoundly upregulated after transfer of this euryhaline pufferfish from FW to SW (Kurita et al, 2008) and after transfer of toadfish (Ruhr et al, 2016) and sea bream (Gregŏrio et al, 2013) from SW to concentrated SW. Consistently, mucosal DIDS, but not serosal DIDS, inhibited HCO 3 - secretion in the sanddab, Citharichthys sordidus (Grosell et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the ion transporter target(s) of GN that lead to increased HCO 3 - secretion, various inhibitors were applied on either mucosal or serosal side of the intestinal epithelia in the Ussing chamber before or after GN administration. The inhibitors applied on the mucosal side were bumetanide, DPC and DNDS/DIDS since, in our earlier studies, GN inhibited NKCC2 and stimulated Cl - channel in the eel (Ando et al, 2014; Ando and Takei, 2015), and since UGN inhibited Pat-1 in the toadfish (Ruhr et al, 2016). DNDS/DIDS was also applied to the serosal side to evaluate the role of basolateral AE and NBC that transport HCO 3 - into the cell.…”
Section: Methodsmentioning
confidence: 99%
“…The combined effect of these processes, in addition to other ion-absorbing pathways, renders the fluid osmolality in the intestine similar to that of the extracellular fluids and allows for efficient water absorption that is coupled to Na + and Cl − absorption (Skadhauge, 1969(Skadhauge, , 1974. Even though net water absorption and the mechanisms that facilitate it are vital to the survival of teleosts living in seawater, recent studies reveal regionspecific areas of the intestine that display net secretory functions, at least periodically (Ruhr et al, 2014(Ruhr et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In the Gulf toadfish, Opsanus beta (Goode and Bean, 1880), members of the homologous guanylin family of intestinal peptides [guanylin, uroguanylin and renoguanylin (RGN)] reverse ion absorption in the posterior intestine, but not in the anterior region (Ruhr et al, 2014). This reversal also corresponds to RGNstimulated water secretion in the posterior intestine and rectum, but not in the anterior intestine (Ruhr et al, 2014(Ruhr et al, , 2016. The switch from net ion absorption to net ion secretion (from mucosa-to-serosa to serosa-to-mucosa) seems to be caused primarily by inhibiting ion absorption by the Na + /K + /Cl − -cotransporter type 2 (NKCC2) and limiting HCO 3 − /Cl − exchange activity, as well as activating Cl − secretion through the apical cystic fibrosis transmembrane conductance regulator (CFTR) channel (Ruhr et al, 2014(Ruhr et al, , 2015(Ruhr et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%